Optimization of gradient-echo MR for calcium detection. - Henkelman, M; Kucharczyk, W (American Journal of Neuroradiology, 1994)
PURPOSE To determine optimal MR gradient-echo sequences for the visualization of calcium in neurologic MR. METHOD The dependence of signal intensity and image contrast on the imaging parameters repetition time, echo time, flip angle, and spoiling were measured for hydroxyapatite samples. Calculations of signal intensity were shown to correspond to these measures. RESULTS Optimum detectability was obtained with an echo time of 29 msec and was independent of spoiling. As repetition time ranged from 30 msec to 700 msec, the optimal flip angle ranged from 17 degrees to 66 degrees. CONCLUSIONS Gradient-echo sequences that optimize the contrast for detection of calcium in neurologic imaging have been determined.